No‐shows to hidradenitis suppurativa clinic visits: Patient perspectives - Natalie M. Fragoso; Rahul Masson; Terri Shih; Tiffany Mayo; Ginette Okoye; Vivian Y. Shi; Jennifer L. Hsiao (Wiley, 2024)
Abstract Background Hidradenitis suppurativa (HS) is a debilitating chronic inflammatory skin condition that typically requires consistent care. Contributory factors to why patients with HS miss their clinic appointments have not been investigated. Objectives This article seeks to characterise reasons that HS patients do not keep their appointments and identify strategies to minimise no‐show rates and improve delivery of care to HS patients. Methods An anonymous survey was distributed to online HS support groups. Results Of the 254 respondents, 18.9% reported ever missing an appointment for HS. Common reasons for missing an appointment include: patient was experiencing an HS flare (72.9%), prior poor experience with a healthcare provider (54.2%) or healthcare staff member (37.5%), embarrassment of condition (41.7%), and distrust that the appointment would help with management of HS (39.6%). Respondents who were non‐White, who were disabled, or who had lower socioeconomic status were more likely to have missed an appointment (p < 0.05). Conclusions This study highlights areas where dermatologists may help improve appointment attendance, including encouraging patients to seek care during flares and striving to optimise the patient experience.